2006
DOI: 10.1530/eje.1.02097
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of various biochemical parameters for the diagnosis of pheochromocytoma in patients with adrenal mass

Abstract: Objective: Pheochromocytomas are neoplasms generally characterized by the autonomous production of catecholamines. This study compared various biochemical parameters for the diagnosis of adrenal pheochromocytoma in patients with adrenal mass. Design: One hundred and fifty subjects were studied, including 24 histologically proven pheochromocytomas, 17 aldosterone-secreting and 21 cortisol-secreting adrenal adenomas and 30 nonfunctioning adrenal masses, 16 patients with essential hypertension and 42 healthy norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
1
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 16 publications
11
69
1
5
Order By: Relevance
“…As with Sawka et al (40) we found a better mean specificity with urinary assays (98.2%, range from 96.9 to 100%) than with plasma ones (93.6%, range from 89.7 to 98.6%). This is valuable for the detection of pheochromocytomas in a sporadic context, where the best possible specificity is required.…”
Section: Controls (Nz71)supporting
confidence: 89%
“…As with Sawka et al (40) we found a better mean specificity with urinary assays (98.2%, range from 96.9 to 100%) than with plasma ones (93.6%, range from 89.7 to 98.6%). This is valuable for the detection of pheochromocytomas in a sporadic context, where the best possible specificity is required.…”
Section: Controls (Nz71)supporting
confidence: 89%
“…This compares with previously reported diagnostic specificities for plasma free metanephrines measured by LCEC at the same center of 85 % [9], and at the NIH of 89 % [8]. In further contrast, for plasma free metanephrines measured by RIA, the diagnostic specificity was 79 % [10].…”
Section: Future Challenges For Effective Diagnosissupporting
confidence: 65%
“…Plasma free metanephrines showed superior combined diagnostic sensitivity and specificity over all other tests examined, including urinary and plasma catecholamines, urinary vanillylmandelic acid and urinary total and fractionated metanephrines. The high diagnostic sensitivity of measurements of plasma free metanephrines has now been independently confirmed by 4 other groups of investigators [7,[9][10][11]. All together, the five independent studies -with 336 patients with pheochromocytoma and close to 2 500 patients in whom the tumor was excluded -have indicated an overall diagnostic sensitivity of 98 % and specificity of 92 % for measurements of plasma free metanephrines (Table 1).…”
Section: Current Progress In Diagnosismentioning
confidence: 64%
See 1 more Smart Citation
“…Some papers have reported a superiority of plasma-free MA assay compared with urine total MA assay (21,30). This study also follows this trend.…”
Section: Clinical Considerationssupporting
confidence: 79%